Synthesis and characterization of lignin-poly lactic acid film as active food packaging material. (24th August 2021) - Chaubey, Ankita; Aadil, Keshaw R.; Jha, Harit
ABSTRACT: The present work describes the synthesis, characterisation and antimicrobial activity of lignin-polylactic acid (PLA) blended film. Film was prepared using co-polymerisation reaction of lignin and lactic acid in the presence of stannous chloride as a catalyst and poly(vinyl alcohol) to get the uniform film. The properties of the film was studied by scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA), respectively. The lignin-PLA film demonstrated a significant decrease in swelling ratio and tensile strength in contrast to PLA film. SEM analysis revealed proper blending of lignin into PLA matrix with slightly rough surface. Film was thermostable and amorphous in nature as confirmed from the thermal study and XRD analysis, respectively. Further, significant improvement was observed in antimicrobial activity and biodegradability of PLA film after addition of lignin, which suggest the putative application of lignin-PLA film as the food packaging and mulch film materials.